Underwriting and rating issues in Islamic insurance : developing an alternative model for the general Islamic insurance industry - Ayinde, Olorogun Lukman (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2015)
Islamic financial institutions (IFIs) emerged as viable alternatives to conventional financial institutions. The Islamic insurance scheme is a vital ancillary to Islamic financial institutions providing services similar to that of conventional insurance. Islamic insurance however, differs from conventional insurance schemes in terms of ownership and forms of contract. Nonetheless, there have been calls by some contemporary Islamic jurists along with a number of Islamic insurance practitioners, that the Islamic insurance industry is currently not adequately empowering the industry in terms of growth, standardisation, and unification of regulations at both academic and market levels. Above all, it is failing to create sufficient competitive advantage for Islamic insurance against its conventional counterpart. Various efforts from state authorities, academics, and major market players to resolve these problems such as lack unified legal rulings, erroneous theory, and lack of enough expertise have thus far proved insufficient or bellied with flaws. With this in mind, the shortcomings in underwriting and rating of insurance products practices, which are central to insurance (conventional and Islamic alike), have gained little or no attention from academics and practitioners alike. Thus, this research generally, was concerned about the extent of reliability of Islamic insurance at academic and professional levels. In order to achieve the objectives of this research, qualitative research methods with dedicated analysis were employed as major tools to investigate and answer the questions. During the course of the investigation, a number of issues were discovered such as non-comprehensive definition, multiple trademark, erroneous theory and concepts, inconsistence models of operation, multiple and unstandardized juristic rulings etc. The research addresses these fundamental problems including provision of detailed definition, suggested universal trademark, developed new theory, proposed and proved Kafālah as an alternative operational model for the Islamic insurance industry, as well provided underwriting and rating considerations based on the Kafālah model from an Islamic perspective. To advance the adequateness of this research, the researcher provided tentative procedures of adopting Kafālah into the Islamic insurance discourse at both academic and market levels.